Manipulation of innate immune response: lessons from shigella - Sansonetti, Philippe (Henry Stewart Talks, 2009)
Microbial immunology: understanding how Shigella, through its capacity to invade the gut epithelium, causes its inflammatory destruction, Identification of the bacterial effectors that regulate the mucosal inflammatory response thus facilitating bacterial colonisation and invasion of the gut
Archived at 2021/02/25